SAT0263 Biologic Therapy, Time to Low Disease Activity, and Effect of Mono Vs. Background Oral Dmard Therapy Among Psoriatic Arthritis Patients in a US Registry. (23rd January 2014) - Mease, P.; Collier, D.; Saunders, K.; Grant, S.; Bitman, B.; Chaudhari, M.; Greenberg, J.
Abstract : Background: Registry data regarding biologic DMARD therapy as a mono or combo (combined with a traditional oral DMARD) in subjects with PsA is limited. In a study of PsA patients in the NOR-DMARD registry similar responses to biologic therapy with/without concomitant MTX were noted. However, it was observed that patients on combo therapy had better drug survival compared to patients on mono therapy. Objectives: Determine baseline characteristics of PsA patients initiating a biologic DMARD, effect of mono vs. background oral DMARD therapy on longevity of staying on that therapy and the time and characteristics from start of therapy to low disease activity (LDA). Methods: Data from the US CORRONA registry, an observational disease-based cohort, was used. Patients with a diagnosis of PsA ≥ 18 yrs of age, who were bio-naïve and initiated a biologic in 2005 or later were included. Survival analyses were performed using Kaplan-Meier curves estimating time on therapy since initiating a biologic, either as mono or combo therapy. Proportional hazard models were used to identify factors associated with risk of therapy change since initiation and events were censored at the last follow-up visit if change of event was not observed. In order to control for channeling bias, Propensity Score (PS) matching was used. Median time from initiation to LDA was calculated. Results: 531 biologic naïve PsA patients met the inclusion criteria, with 60% initiating combo therapy and 40% initiating monotherapy. About 52% were female, average age of 52 yrs, mean duration of PsA was 6.4 yrs, mean CDAI was 11.6 and mean MD global assessment of skin of 19.5. Patients initiating combo therapy had a slightly higher mean tender/swollen joint count, CDAI, MD global assessment of skin. Median time on combo and mono therapy since initiation in the PS matched patients was 14.2m and 20.5m respectively (Figure 1 ). Significant factors associated with changing the therapy since biologic initiation were Hispanic/Latino (HR 0.4), higher CDAI (HR 1.02), higher mHAQ (HR 1.7), current use of any non-TNF (HR 1.8) and history of non-biologic DMARD use (HR 1.8). PS matched results showed that patients on combo therapy were at higher risk of changing the therapy (HR 1.4 p=0.01). The median time to LDA from biologic initiation in PS matched patients was 16.7m and 16.6m for patients on combo and mono therapy respectively (Figure 1 ). Significant factors associated with achievement of LDA from biologic initiation were age (HR 0.98), gender (HR 0.74), BMI (HR 0.95), CDAI (HR 0.89), and mHAQ (HR 0.15). Image/graph: Conclusions: In this observational cohort of PsA patients, patients continued to stay on their initial biologic therapy for an average of 1.4 yrs. PsA patients demonstrated similar ability to achieve LDA whether on mono or combo therapy when the sample was PS matched. Being on combo therapy did not offer an advantage in terms of cycling off the biologic. Acknowledgements: Research funded by CORRONA and a data subscription from Immunex Corporation, a wholly owned subsidiary of Amgen Inc. and by Wyeth, which was acquired by Pfizer Inc. in October 2009. Disclosure of Interest: P. Mease Grant/research support from: Celgene, Merck, Novartis, Abbvie, Amgen, BiogenIdec, BMS, Genentech, Janssen, Lilly, Pfizer, UCB, Consultant for: Celgene, Merck, Novartis, Abbvie, Amgen, BiogenIdec, BMS, Genentech, Janssen, Lilly, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BiogenIdec, BMS, Genentech, Janssen, Lilly, Pfizer, UCB, D. Collier Shareholder of: Amgen, Employee of: Amgen, K. Saunders Employee of: CORRONA, Inc., S. Grant Employee of: Axio LLC, B. Bitman Shareholder of: Amgen, Employee of: Amgen, M. Chaudhari Employee of: Axio LLC, J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: Astra Zeneca, CORRONA, Novartis and Pfizer